EFFECT OF SOWING DATE ON GROWTH AND YIELD OF FOUR RADISH (RAPHANUS SATIVUS L .) VARIETIES - Amur A. H . Al – juboori; Shamil . Y . H . Al-hamdani; Merwa . M . Hamdon (Mesopotamia Journal of Agriculture)
An experiment was conducted in the Vegetable field of Horticulture and landscape Department College of Agriculture and Forestry University of Mosul, during the growing season of (2018 – 2019) to study the effect of sowing dates (20th Oct; 10th Nov) on growth and yield of four radish varieties Red Local (V1); Black Local (V2); Turkish (V3) and Syrian (V4) of radish All the growth parameters such as, number of leaves, leaf area, root-shoot ratio  plant weight, root weight, root length, root diameter, yield of root(24.703) t h-1 were significantly increased with sowing 20th Oct compared with other sowing dates.    The effect of varieties Surry superior in Root weight (152.43 g) and root to shoot ratio (2.07) and diameter of root (7.00 cm) and total root yield (25.4 t h-1) compared with other varieties. Interaction between sowing dates and varieties showed that sowing on 20th Oct significant on growth and yield such as Number of leaves per plant, Leaf area and root yield. The fresh weight of leaves was supreme (176.97 g ) in Black Local, and root length (8.63 cm) .